Is the Theta/Beta EEG Marker for ADHD Inherently Flawed?. Issue 9 (July 2018) - Saad, Jacqueline F.; Kohn, Michael R.; Clarke, Simon; Lagopoulos, Jim; Hermens, Daniel F.
Objective: Despite advances in our understanding of ADHD as a neurodevelopmental disorder, robust biomarkers are yet to be established in clinical practice. More than 40 years of electroencephalography (EEG)-based research has culminated in the recent Food and Drug Administration (FDA) approval of the theta/beta (EEG power) ratio (TBR) as a diagnostic marker of ADHD.Method: This review article focuses on resting-state EEG power research in ADHD.Results: Inconsistent findings in the literature and suggestions of reduced specificity threaten the utility of TBR as a biomarker of ADHD. The use of fixed EEG bands may be a significant limitation, particularly in youth, and alternative approaches are needed.Conclusion: We propose that a personalized theta-to-alpha cut point or "transition frequency" is a better frame of reference for the measurement of TBR. Such an approach is better placed to test maturational lag and cortical hypoarousal models of ADHD and may in turn have greater utility in supporting diagnosis.